2023
DOI: 10.1021/acs.jafc.3c01251
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Umami Peptides in Chicken Breast Soup through a Sensory-Guided Approach and Molecular Docking to the T1R1/T1R3 Taste Receptor

Abstract: Ultrafiltration combined with nanoliquid chromatography quadrupole time-of-flight mass spectrometry (nano-LC-QTOF-MS) and sensory evaluation was used to separate and identify umami peptides in chicken breast soup. Fifteen peptides with umami propensity scores of >588 were identified from the fraction (molecular weight ≤1 kDa) using nano-LC-QTOF-MS, and their concentrations ranged from 0.02 ± 0.01 to 6.94 ± 0.41 μg/L in chicken breast soup. AEEHVEAVN, PKESEKPN, VGNEFVTKG, GIQKELQF, FTERVQ, and AEINKILGN were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 40 publications
4
27
0
Order By: Relevance
“…Among them, peptides TEEMEEMRRKL and DKDGKGKIPEEY had the lowest Δ E docking , respectively, reaching −210.977 and −207.577 kcal/mol. It is worthwhile to be concerned about the absence of a correlation between docking energy and peptide length, which is in line with the results of the Zhang et al study. Previous research has demonstrated that lower binding energies indicate greater structural stability of umami peptides and receptors, which may make umami easier to produce. , As can be seen from Table , the CHARMm binding energies (Δ E binding ) of the 36 umami peptides varied considerably, with the lowest Δ E binding of −437.055 kcal/mol for ISIEDVEESRNK and the highest Δ E binding of 9.5305 kcal/mol for EGEEEWDREG.…”
Section: Resultssupporting
confidence: 78%
“…Among them, peptides TEEMEEMRRKL and DKDGKGKIPEEY had the lowest Δ E docking , respectively, reaching −210.977 and −207.577 kcal/mol. It is worthwhile to be concerned about the absence of a correlation between docking energy and peptide length, which is in line with the results of the Zhang et al study. Previous research has demonstrated that lower binding energies indicate greater structural stability of umami peptides and receptors, which may make umami easier to produce. , As can be seen from Table , the CHARMm binding energies (Δ E binding ) of the 36 umami peptides varied considerably, with the lowest Δ E binding of −437.055 kcal/mol for ISIEDVEESRNK and the highest Δ E binding of 9.5305 kcal/mol for EGEEEWDREG.…”
Section: Resultssupporting
confidence: 78%
“…Peptide EVNYDFGGK formed a total of eight hydrogen bonds with residues Asp192, Gln195, Phe274, Gln316, Arg317, and Lys335, and hydrophobic interactions with 12 residues, including Asp218, Tyr220, and Ser276 (Figure D). Among the amino acid residues interacting with the umami peptides, Ser107, Ser148, Thr149, Ala170, Ser172, Gln195, Asp218, Tyr220, Ser276, and Arg277, have been reported as important residues for receptor T1R1/T1R3 complex to bind umami peptides and recognize umami taste. ,,, According to the results of intermolecular interaction force, it indicated that peptide EVNYDFGGK may bind most tightly to receptor T1R1/T1R3 complex among these four umami peptides. Moreover, this study further investigated the interaction forces between the typical umami peptide KGDEESLA and the receptor T1R1/T1R3, as well as the potential nonumami peptide EPVSL and the receptor T1R1/T1R3.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking and molecular dynamics simulation methods have been widely used to investigate the interactions between small molecules and receptors. Zhang et al have shown that the serine residues of umami peptides were the frequently observed binding sites in T1R1/T1R3 using the molecular docking method . Huang et al used the molecular docking to analyze the interactions between myofibrillar protein and phenolic compounds and identify their binding modes and sites .…”
Section: Introductionmentioning
confidence: 99%